SIMULASI TOPOLOGI JARINGAN BERBASIS IOT UNTUK PERANGKAT RUMAH TANGGA MENGGUNAKAN CISCO PACKET TRACER - Meidianto, Meidianto; Anggeliani, Cynthia; Angreyani, Jeny; Pernando, Yonky (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2025)
Abstract: This study aims to simulate the implementation of the Internet of Things (IoT) in household devices using Cisco Packet Tracer. In this simulation, various devices such as smart lights, fans, air conditioners, automatic doors, automated windows, and smoke detectors were successfully controlled via smartphone with the assistance of a Home Gateway. The research was conducted using a structured simulation method, starting from planning to network topology evaluation. The simulation results show that the integration of IoT devices can function efficiently and stably. Each testing scenario from unlocking doors and adjusting fan speed to smoke detection was executed successfully and demonstrated real-time responses. This success highlights that Cisco Packet Tracer is an effective and cost-efficient tool for designing and testing smart home systems before real-world implementation. Moreover, the ease of controlling devices through mobile gadgets adds an extra layer of convenience for users. This study provides practical and applicable insights into the benefits of IoT technology in household settings and opens further opportunities for future smart home development. Keyword: Internet of Things (IoT); Cisco Packet Tracer; Smart Home; Home Gateway; Network Simulation Abstrak: Penelitian ini bertujuan untuk mensimulasikan penerapan Internet of Things (IoT) dalam perangkat rumah tangga dengan menggunakan Cisco Packet Tracer. Dalam simulasi ini, berbagai perangkat seperti lampu pintar, kipas angin, AC, pintu otomatis, jendela otomatis, dan detektor asap berhasil dikendalikan melalui smartphone dengan bantuan Home Gateway. Proses penelitian ini dilakukan dengan metode simulasi yang terstruktur, mulai dari perencanaan hingga evaluasi topologi jaringan. Hasil simulasi menunjukkan bahwa integrasi perangkat IoT dapat berfungsi dengan efisien dan stabil. Setiap skenario pengujian, mulai dari membuka pintu, mengatur kecepatan kipas, hingga mendeteksi asap, berhasil dilaksanakan dengan baik dan menunjukkan respons secara real-time. Keberhasilan ini menggarisbawahi bahwa Cisco Packet Tracer adalah alat yang efektif dan ekonomis untuk merancang serta menguji sistem rumah pintar sebelum diterapkan dalam kenyataan. Selain itu, kemudahan dalam mengontrol perangkat melalui gadget mobile memberikan kenyamanan tambahan bagi pengguna. Penelitian ini memberikan wawasan praktis dan aplikatif tentang manfaat teknologi IoT dalam rumah tangga serta membuka peluang lebih lanjut untuk pengembangan smart home di masa mendatang. Kata kunci: Internet of Things (IoT); Cisco Packet Tracer; Smart Home; Home Gateway; Simulasi Jaringan